Preparation method of precious metal monatomic loaded TiO2 photocatalyst
By creating oxygen vacancy defects on TiO2 nanocarrier and adjusting the pH value using (NH4)2CO3 solution, stable loading of precious metal single atoms is achieved, solving the problem of low performance of precious metal single atom-loaded TiO2 catalysts in the prior art, significantly improving The hydrogen production rate of photolysis of hydrogen production and the stability of the catalyst.
Patent Information
- Application Number
- CN202411258753.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art is difficult to prepare stable and efficient single-atom-supported TiO2 catalysts for precious metals, resulting in low catalytic performance, especially in the process of photohydrogen production of hydrogen.
By creating oxygen vacancies on TiO2 nanocarrier, and adjusting the pH value using (NH4)2CO3 solution, controlling the dropping process of precious metal precursors, achieving stable loading of precious metal single atoms and forming a single atom-loaded TiO2 photocatalyst.
It improves the stability and catalytic activity of the catalyst, increases the photoresponse range, and significantly increases the hydrogen production rate of photolysis hydrogen production. It has a simple process and low cost, which is suitable for large-scale production.
Smart Images

Figure CN119259033A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a noble metal-loaded TiO2 single-atom composite photocatalyst, belonging to the technical field of catalyst synthesis. Technical Background
[0002] TiO2 is widely used in the field of photocatalysis due to its stable performance, non-toxicity, non-irritation and low cost. However, since TiO2 is a wide bandgap semiconductor (anatase E g= 3.2eV, rutile E g= 3.0eV), can only respond under ultraviolet light below 387nm, and the utilization rate of light energy is extremely low. At the same time, the electron holes generated by light excitation will be quenched at a very fast rate in most cases, and only a small number of carriers can participate in the photocatalytic reaction on the surface, resulting in the reduction of TiO2 catalytic performance. In the process of photolysis of water to produce hydrogen, the hydrogen production rate is extremely slow, so TiO2 needs to be modified to improve its catalytic efficiency.
[0003] After noble metals are deposited on the TiO2 surface, photogenerated electrons will migrate from TiO2 to the noble metal surface with a lower Fermi level, forming a Schottky barrier, which can effectively separate the photogenerated charges, extend the lifetime of excited electrons, and reduce the recombination rate of photogenerated electrons and holes; at the same time, the loading of noble metals reduces the bandgap width of TiO2, broadens the light response range of the composite TiO2 catalyst, and improves its light energy utilization rate.
[0004] When the noble metal loading is reduced from nanoclusters to single atoms, the atomic utilization rate reaches the maximum, and the catalytic activity of a single atom is much higher than that of a noble metal cluster. However, as the metal particles become smaller, the surface free energy increases, and the general loading method cannot obtain a stable single-atom loading. Even if the single-atom state is temporarily dispersed, it will quickly agglomerate into clusters due to the high surface energy, thereby deactivating the catalyst. At present, it is still a difficult problem to prepare low-cost and stable noble metal single-atom loaded TiO2 catalysts. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a precious metal single-atom loaded TiO2 photocatalyst with mild conditions, simple process, easy quantification and easy large-scale production. By adding a specific pH adjuster, the method solves the shortcomings of other types of adjusters in adjusting pH values, such as large fluctuations, difficulty in quantification and poor repeatability.
[0006] The implementation process of the present invention is as follows: A method for preparing a noble metal single atom-loaded TiO2 photocatalyst comprises the following steps: (1) Preparation of TiO2 nanocarriers; (2) reducing the TiO2 nanocarrier at 200-300°C in a hydrogen-argon mixed atmosphere to obtain a TiO2 nanocarrier rich in oxygen vacancy defects; (3) dispersing the TiO2 nanocarrier rich in oxygen vacancy defects in deionized water, adding (NH4)2CO3 solution to adjust the pH of the system to 8.5-8.9, and obtaining a TiO2 suspension; (4) adding a noble metal precursor solution dropwise to the TiO2 suspension to control the theoretical loading of the noble metal to be 0.05-0.1%, wherein the noble metal precursor is H2PtCl6·6H2O, PdCl2 or HAuCl4; (5) After being thoroughly stirred, the solution is centrifuged, the precipitate is collected, washed, and dried, and then placed in a hydrogen-argon mixed atmosphere at 240-260°C for reduction treatment to obtain a single-atom-loaded TiO2 photocatalyst.
[0007] In the above step (1), the TiO2 nanocarrier is preferably in the shape of a flower cluster. One of the preparation methods thereof is as follows: Butyl titanate and glacial acetic acid in a volume ratio of 1:20-1:50 are placed in a closed reactor, mixed evenly and reacted fully at 120-180°C, and the precipitate is collected and calcined at 350-450°C in an air atmosphere to obtain cluster-shaped TiO2 nanospheres.
[0008] In the above steps (2) and (5), the volume ratio of hydrogen to argon in the hydrogen-argon mixed gas is H2:Ar=1:8~1:9.5.
[0009] In the above step (3), the concentration of the (NH4)2CO3 solution is 0.5~2 mol / L.
[0010] In the above step (4), the theoretical loading is the mass percentage of the precious metal to TiO2. The precious metal precursor is preferably H2PtCl6·6H2O. The precious metal is loaded on TiO2 in a single-atom state, and its loading can reach up to 0.1wt%, which is 0.05wt% higher than other methods.
[0011] The application of the noble metal single atom-loaded TiO2 photocatalyst prepared by the above method in photocatalytic water decomposition.
[0012] Features, advantages and positive effects of the present invention: (1) It is well known that in the preparation of single-atom catalysts by precipitation method, the selection of alkaline solution is crucial to the effect of single-atom loading. The present invention uses (NH4)2CO3 as a pH regulator, which has a better buffering effect than the commonly used ammonia solution, and is also easier to obtain a single-atom loaded catalyst with large loading and stable properties than other alkaline solutions (such as Na2CO3, NaOH, etc.); (2) The reaction conditions of the present invention are mild, and the morphology of the original TiO2 can be maintained unchanged to the greatest extent; (3) In order to overcome the deactivation problem of single-atom catalysts, the present invention creates oxygen vacancy defects on the TiO2 surface, so that metal single atoms occupy the original oxygen vacancy positions and are anchored by surrounding atoms, thereby obtaining a stable single-atom-loaded TiO2 composite photocatalyst; (4) The (NH4)2CO3 solution used in the preparation method of the present invention has little environmental pollution, a simple preparation process, easy reaction conditions, low consumption of precious metals, large single-atom loading, stable catalyst with good performance, low production cost, and potential for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is the XRD pattern of the catalyst synthesized in Example 1; Figure 2 This is the SEM image of the flower-shaped nanosphere TiO2 synthesized in Example 1; Figure 3 This is a SEM image of the Pt / TiO2 catalyst synthesized in Example 1; Figure 4 This is the SEM image of the hollow sphere TiO2 synthesized in Example 2; Figure 5 This is a SEM image of the Pt / TiO2 catalyst synthesized in Example 2; Figure 6 This is the SEM image of the solid nanosphere TiO2 synthesized in Example 3; Figure 7 This is a SEM image of the Pt / TiO2 catalyst synthesized in Example 3; Figure 8 The Pt4f map of the XPS of the Pt / TiO2 catalyst synthesized in Example 1; Fig. 9 Evaluation of the hydrogen production effect of the catalyst prepared under different pH and different buffer conditions in Example 1; Fig.10 This is the HAADF-STEM image of the single atom catalyst prepared in Example 1. DETAILED DESCRIPTION
[0014] The following is an explanation of the synthesis method of the present invention and the superiority of the photocatalyst prepared by the present invention in producing hydrogen by photolysis of water by using specific examples, the purpose of which is to better understand the content of the present invention rather than to limit the protection scope of the present invention. Example
[0015] Add 30 ml of glacial acetic acid to 50 ml of dry polytetrafluoroethylene liner, measure 1 ml of butyl titanate and quickly inject it into it, cover and seal, and mix it evenly by ultrasonication for 20 minutes. After the ultrasonication is over, put the liner into the hydrothermal reactor and tighten it, react at 140°C for 12 hours, and take it out after the reactor cools to room temperature. Transfer the reaction product into a centrifuge tube and centrifuge it. The centrifuge speed and time are set to 8500r / min and 2min respectively. Then take out and decant the supernatant, and wash the solid alternately with anhydrous ethanol and water 3 times. Then dry it in a drying oven at 80°C for 4h. After drying, the powder is placed in a muffle furnace and calcined at 400°C for 2h, with a heating rate of 2ºC / min. After natural cooling, TiO2 flower cluster nanospheres are obtained. The XRD pattern of the obtained TiO2 is as follows Figure 1 As shown; the prepared TiO2 SEM pictures Figure 2 shown.
[0016] The TiO2 with flower-cluster nanosphere morphology was placed in a hydrogen-argon mixed atmosphere (10% H2) and reduced at 200°C for 2h with a heating rate of 2°C / min to create sufficient oxygen vacancy defects.
[0017] Take 0.5g of oxygen vacancy-rich TiO2 and disperse it in 100ml of deionized water. Ultrasonicate for 15min and continue stirring. Add 1M (NH3)2CO3 solution to it until the pH is 8.7. After stirring for 15min, slowly add 335μL H2PtCl6·6H2O solution (7.72mmol / L). Stir for 5h in the dark, then wash with deionized water by centrifugation 3 times, and dry in vacuum at 60ºC. Put the dried sample into a tube furnace and reduce it at 250ºC for 2h in a hydrogen-argon mixed atmosphere (H2:Ar=1:9 V / V) with a heating rate of 2ºC / min. The SEM image of the prepared Pt single atom-loaded TiO2 composite photocatalyst is shown below. Figure 3 As shown, it can be seen that the morphology is basically unchanged; the XPS Pt4f map is as follows Figure 8 As shown; Fig.10 The HAADF-STEM image of the prepared single-atom catalyst shows intuitively that Pt atoms are doped on the TiO2 surface in the form of single atoms. Example
[0018] Add 30ml of glacial acetic acid to 50ml of dry polytetrafluoroethylene liner, measure 1ml of titanate butyl ester and quickly inject it, cover and seal, and mix it evenly by ultrasonication for 20min. After the ultrasonication, put the liner into the hydrothermal reactor and tighten it, react at 140°C for 12h, and take it out after the reactor cools to room temperature. Transfer the reaction product into a centrifuge tube for centrifugation, and set the centrifuge speed and time to 8500r / min and 2min respectively. Then take out and decant the supernatant, and wash the solid alternately with anhydrous ethanol and water 3 times. Then dry it in a drying oven at 80°C for 4h. After drying, the powder is placed in a muffle furnace and calcined at 400°C for 2h, with a heating rate of 2ºC / min. After natural cooling, TiO2 flower-like nanospheres are obtained.
[0019] The TiO2 with flower-like nanosphere morphology was placed in a hydrogen-argon mixed atmosphere (H2:Ar=1:9V / V) and reduced at 200°C for 2h with a heating rate of 2°C / min to create sufficient oxygen vacancy defects.
[0020] Take 0.5g of oxygen vacancy-rich TiO2 and disperse it in 100ml of deionized water, ultrasonicate for 15min and continue stirring, add 1M (NH3)2CO3 solution to it until the pH is 8.7, stir for 15min, then slowly add 210μLPdCl2 solution (22.4mM), stir for 5h in the dark, then wash with deionized water by centrifugation for 3 times, and dry in vacuum at 60ºC. Put the dried sample into a tube furnace and reduce it at 250ºC for 2h in a hydrogen-argon mixed atmosphere (H2:Ar=1:9 V / V), with a heating rate of 2ºC / min.
[0021] Take 0.05g sample, 90ml deionized water, 10ml methanol, put into the photocatalytic reaction device, use 300w xenon lamp to irradiate, measure the amount of hydrogen produced every 1h. As a control group, take 0.05g pure TiO2 rich in oxygen vacancies and measure the hydrogen production rate in the same way.
[0022] By comparing the hydrogen production rates, the hydrogen production rate of pure TiO2 is 42.672 μmol / g·h, and the hydrogen production rate of TiO2 composite photocatalyst loaded with 0.1% Pd single atoms is 1480.12 μmol / g·h. Compared with Pt single atom loading, 0.1wt% Pt single atom loading is the best choice. Example
[0023] Add 30ml of glacial acetic acid to 50ml of dry polytetrafluoroethylene liner, measure 1ml of titanate butyl ester and quickly inject it, cover and seal, and mix it evenly by ultrasonication for 20min. After the ultrasonication, put the liner into the hydrothermal reactor and tighten it, react at 140°C for 12h, and take it out after the reactor cools to room temperature. Transfer the reaction product into a centrifuge tube for centrifugation, and set the centrifuge speed and time to 8500r / min and 2min respectively. Then take out and decant the supernatant, and wash the solid alternately with anhydrous ethanol and water 3 times. Then dry it in a drying oven at 80°C for 4h. After drying, the powder is placed in a muffle furnace and calcined at 400°C for 2h, with a heating rate of 2ºC / min. After natural cooling, TiO2 flower-like nanospheres are obtained.
[0024] The TiO2 with flower-like nanosphere morphology was placed in a hydrogen-argon mixed atmosphere (H2:Ar=1:9 V / V) and reduced at 200°C for 2h with a heating rate of 2°C / min to create sufficient oxygen vacancy defects.
[0025] Take 0.5g of oxygen vacancy-rich TiO2 and disperse it in 100ml of deionized water, ultrasonicate for 15min and continue stirring, add 1M (NH3)2CO3 solution to it until the pH is 8.7, stir for 15min, slowly add 230 μL HAuCl4 solution (1g / 250ml), stir for 5h in the dark, then wash with deionized water by centrifugation for 3 times, and dry in vacuum at 60°C. Put the dried sample into a tube furnace and reduce it at 250°C for 2h in a hydrogen-argon mixed atmosphere (H2:Ar=1:9 V / V), with a heating rate of 2°C / min.
[0026] Take 0.05g sample, 90ml deionized water, 10ml methanol, put into the photocatalytic reaction device, use 300w xenon lamp to irradiate, measure the amount of hydrogen produced every 1h. As a control group, take 0.05g pure TiO2 rich in oxygen vacancies and measure the hydrogen production rate in the same way.
[0027] By comparing the hydrogen production rates, the hydrogen production rate of pure TiO2 is 42.672 μmol / g·h, and the hydrogen production rate of the TiO2 composite photocatalyst loaded with 0.1% Au single atoms is 1366.8 μmol / g·h. Compared with the Pt single atom loading, 0.1wt% Pt single atom loading is still the best catalyst. Example
[0028] In order to better screen the vector and experimental conditions, the present invention designs the following technical solutions: (1) Replace (NH3)2CO3 with aqueous ammonia and 1M sodium carbonate solution, keep pH = 8.7, and keep other conditions unchanged to prepare two catalysts for comparison.
[0029] Take 0.05g sample, 90ml deionized water, 10ml methanol, put into the photocatalytic reaction device, use 300w xenon lamp to irradiate, measure the amount of hydrogen produced every 1h. As a control group, take 0.05g pure TiO2 rich in oxygen vacancies and measure the hydrogen production rate in the same way.
[0030] (2) By changing the (NH3)2CO3 concentration and adjusting the pH to 8 and 9.3 respectively, and keeping other conditions unchanged, two catalysts were prepared for comparison. Example
[0031] Fix the three-necked flask in an oil bath, add 85ml of deionized water, 10.5ml of styrene, and 0.5ml of methyl acrylate in turn, and place a magnetic bar for continuous stirring. Put a sealing leather cover, a condensation reflux tube, and a nitrogen pipeline on the top of the three-necked flask in turn, extend the nitrogen pipeline under the solution, and keep nitrogen bubbles coming out continuously for 30 minutes to completely remove the air in the bottle and the liquid. Then adjust the nitrogen until the bubbles come out one by one, turn on the oil bath heating switch and heat it to 70ºC. Use an injection to extract 1ml of sodium persulfate solution (0.03g / ml) and inject it into the reactor, and react at 70ºC for 24h. After the reaction is completed, pour the solution into a glass dish and dry it in a drying oven at 60ºC for 12h to finally obtain a polystyrene microsphere template.
[0032] Take 2g PS microspheres and put them into a round-bottom flask, add 150ml anhydrous ethanol and 1ml deionized water, and ultrasonicate for 30min to completely disperse them. Then fix the reactor in an oil bath and place it under magnetic stirring, add 3ml tetrabutyl titanate and 15ml anhydrous ethanol mixture, install a condensation reflux tube, turn on the heating switch, condense and reflux at 80ºC for 4h, filter after the reaction, wash with anhydrous ethanol three times, and then wash with deionized water three times to prevent the unhydrolyzed tetrabutyl titanate from hydrolyzing and affecting the morphology.
[0033] The core-shell structured product was collected and heated to 250°C at 1°C / min in a muffle furnace for 1 hour, then heated to 300°C for 2 hours, 350°C for 1 hour, and finally 400°C for 3 hours to ensure that the TiO2 shell remained intact during the template removal process and the PS microspheres were completely removed. The resulting TiO2 hollow spheres were obtained. The morphology of the synthesis is shown in Figure 4 .
[0034] The hollow spherical TiO2 was placed in a hydrogen-argon mixed atmosphere (10% H2) and reduced at 200°C for 2h with a heating rate of 2°C / min to create sufficient oxygen vacancy defects.
[0035] Take 0.5g of TiO2 with oxygen vacancy-rich hollow spherical morphology and disperse it in 100ml of deionized water. Ultrasonicate for 15 minutes, add 1M (NH3)2CO3 solution to it until the pH is 8.7, stir for 15 minutes, and slowly add 335 μL H2PtCl6·6H2O solution (7.72mmol / L) to make its theoretical loading amount 0.1wt.%, stir for 5h in the dark, then wash with deionized water by centrifugation 3 times, and dry in vacuum at 60ºC. Put the dried sample into a tube furnace and reduce it at 250ºC for 2h in a hydrogen-argon mixed atmosphere (H2:Ar=1:9 V / V) with a heating rate of 2ºC / min. The SEM image of the prepared Pt / TiO2 composite photocatalyst is shown in Figure 5 , it can be seen that the morphology has basically not changed.
[0036] The rates of hydrogen production from photocatalytic water splitting were compared between pure hollow sphere TiO2 and loaded Pt / TiO2.
[0037] The hydrogen production effect of pure hollow sphere TiO2 is 39.622 μmol / g·h, and the hydrogen production rate of Pt / TiO2 is 2611.65 μmol / g·h, which is nearly 66 times higher. Example
[0038] Pour 200 ml of diethylene glycol into a beaker and stir continuously at 25°C. Slowly add 3 ml of tetrabutyl titanate dropwise into the beaker, and then stir vigorously for 12 h in the dark.
[0039] Measure 600 ml of acetone and stir vigorously. Slowly pour the reaction solution into acetone and add 2 ml of deionized water. Stir for 90 min in the dark. After the reaction, wash with anhydrous ethanol and deionized water alternately by centrifugation for 3 times, put it in an oven to dry at 80°C, and finally heat the product to 400°C at 2°C / min and keep it for 4h. Figure 6 The SEM image can intuitively show the morphology of the prepared solid sphere.
[0040] Take 0.5g of TiO2 with solid nanosphere morphology rich in oxygen vacancies and disperse it in 100ml of deionized water. Ultrasonicate for 15min, add 1M (NH3)2CO3 solution to it until the pH is 8.7, stir for 15min, and slowly add 335 μL of H2PtCl6·6H2O solution (7.72 mmol / L) to make its theoretical loading amount 0.1wt.%, stir for 5h in the dark, then wash with deionized water by centrifugation 3 times, and dry in vacuum at 60ºC. The dried sample was placed in a tubular furnace and reduced at 250ºC for 2h in a hydrogen-argon mixed atmosphere (H2:Ar=1:9 V / V), with a heating rate of 2ºC / min. The SEM image of the prepared TiO2 composite photocatalyst is shown as follows: Figure 7The morphology did not change before and after loading.
[0041] The rates of hydrogen production from photolysis of water were compared between pure solid nanosphere TiO2 and loaded Pt / TiO2.
[0042] The hydrogen production effect of pure solid nanosphere TiO2 is 28.02 μmol / g·h, and the hydrogen production rate of Pt / TiO2 is 492.78 μmol / g·h, which is also greatly improved.
[0043] Fig. 9 This is a comparison chart of hydrogen production rates of flower-shaped nanosphere TiO2 composite catalysts prepared with different pH and alkaline solutions. Through the comparison of hydrogen production rates, the hydrogen production rate of pure TiO2 is 42.672 μmol / g·h, the hydrogen production rate of the single-atom catalyst prepared by using 1M (NH3)2CO3 as the alkaline solution to adjust the pH is 5102.8 μmol / g·h, the hydrogen production rate of the catalyst prepared by adjusting the pH with ammonia water is 3636.4 μmol / g·h, and the hydrogen production rate of the catalyst prepared by adjusting the pH with sodium carbonate is 4233.2 μmol / g·h; the hydrogen production rate of the catalyst prepared by increasing the ratio of (NH3)2CO3 solution to adjust the pH to 9.3 is 3089.16 μmol / g·h, and the hydrogen production rate of the catalyst prepared by reducing the ratio of (NH3)2CO3 solution to adjust the pH to 8 is 4105.3 μmol / g·h. The hydrogen production rates are greatly improved, among which the single-atom catalyst prepared by the present invention has the best effect.
Claims
1. A method for preparing a noble metal single atom-loaded TiO2 photocatalyst, characterized in that The following steps are involved: (1) Preparation of TiO2 nanocarriers; (2) reducing the TiO2 nanocarrier at 200-300°C in a hydrogen-argon mixed atmosphere to obtain a TiO2 nanocarrier rich in oxygen vacancy defects; (3) dispersing the TiO2 nanocarrier rich in oxygen vacancy defects in deionized water, adding (NH4)2CO3 solution to adjust the pH of the system to 8.5-8.9, and obtaining a TiO2 suspension; (4) adding a noble metal precursor solution dropwise to the TiO2 suspension to control the theoretical loading of the noble metal to be 0.05-0.1%, wherein the noble metal precursor is H2PtCl6·6H2O, PdCl2 or HAuCl4; (5) After being thoroughly stirred, the solution is centrifuged, the precipitate is collected, washed, and dried, and then placed in a hydrogen-argon mixed atmosphere at 240-260°C for reduction treatment to obtain a single-atom-loaded TiO2 photocatalyst.
2. The method for preparing the noble metal single atom-loaded TiO2 photocatalyst according to claim 1, characterized in that: In the above step (1), the TiO2 nanocarrier is preferably a flower cluster-shaped TiO2 nanocarrier.
3. The method for preparing the noble metal single atom-loaded TiO2 photocatalyst according to claim 2, characterized in that The preparation method of flower cluster TiO2 nanocarrier is as follows: place butyl titanate and glacial acetic acid in a volume ratio of 1:20~1:50 in a closed reactor, mix them evenly and react them fully at 120~180°C, collect the precipitate and calcine it at 350~450°C in an air atmosphere to obtain flower cluster TiO2 nanospheres.
4. The method for preparing the noble metal single atom-loaded TiO2 photocatalyst according to claim 1, characterized in that: In the above steps (2) and (5), the volume ratio of hydrogen to argon in the hydrogen-argon mixed gas is H2:Ar=1:8~1:9.
5.
5. The method for preparing the noble metal single atom-loaded TiO2 photocatalyst according to claim 1, characterized in that: In the above step (3), the concentration of the (NH4)2CO3 solution is 0.5~2 mol / L.
6. The method for preparing the noble metal single atom-loaded TiO2 photocatalyst according to claim 1, characterized in that: In the above step (4), the noble metal precursor is preferably H2PtCl6·6H2O.
7. The method for preparing the noble metal single atom-loaded TiO2 photocatalyst according to claim 6, characterized in that: The noble metal is loaded on TiO2 in a single-atom state, and the loading amount is up to 0.1 wt%.
8. The noble metal single atom-loaded TiO2 photocatalyst prepared by the method of claim 1.
9. Use of the noble metal single atom-loaded TiO2 photocatalyst according to claim 8 in photocatalytic water decomposition.
Citation Information
Cited By
Rutile-phase titanium dioxide supported palladium monatomic catalyst and application thereof
CN120679521A